2022
DOI: 10.1186/s12870-022-03847-8
|View full text |Cite
|
Sign up to set email alerts
|

Study of the grafting compatibility of the apple rootstock 12–2, resistant to apple replant diseases (ARD)

Abstract: Background Cultivation of resistant rootstocks can effectively prevent apple replant disease (ARD), and grafting tests are an important means of evaluating the compatibility of rootstocks with scions. Methods The apple rootstocks 12–2 (self-named) and Malus hupehensis Rehd. (PYTC) were planted in a replanted 20-year-old apple orchard. The two rootstocks were grafted with scions of 13 apple varieties. Multiple aboveground physiological parameters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Different rootstocks can induce significant differences in the scion chlorophyll content, which conversely affects photosynthetic rate [ 34 ]. In this regard, photosynthesis increased in the case of high compatible apple rootstock [ 35 ]. By contrast, Irisarri et al [ 36 ] found in the incompatible pear (Williams)/quince (BA29) grafts combination abnormal shape of chloroplasts as well as poor developed membranes lacking grana.…”
Section: Discussionmentioning
confidence: 99%
“…Different rootstocks can induce significant differences in the scion chlorophyll content, which conversely affects photosynthetic rate [ 34 ]. In this regard, photosynthesis increased in the case of high compatible apple rootstock [ 35 ]. By contrast, Irisarri et al [ 36 ] found in the incompatible pear (Williams)/quince (BA29) grafts combination abnormal shape of chloroplasts as well as poor developed membranes lacking grana.…”
Section: Discussionmentioning
confidence: 99%
“…Grafting is a traditional technique of asexual propagation since antiquity for fruit crop improvement, and has been widely used in many horticultural crops, such as apple [ 1 , 2 ], pear [ 3 , 4 ], citrus [ 5 ], and grape [ 6 ]. Certain rootstocks not only affect the adaptability of fruit trees to the natural environment, but also influence tree growth potential and fruit production efficacy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Cucurbitaceae family, pumpkins are used as rootstocks to enhance cold tolerance in cucumber seedlings by boosting the phenylpropanoid metabolism and phytohormones synthesis [ 9 ]. The use of resistant rootstocks in Rosaceae family reveals high resistance of apple scions to apple specific replant disease [ 10 ]. In Solanaceae crops, using Solanum torvum as rootstocks can reduce heavy metal stress by lowering the accumulation of cadmium ions in tomato, eggplant, and pepper scions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%